e-Blitz - Solution to Support Transit Automotive Vehicle Inspection - Carvalho e Silva, Gustavo Henrique; Cassela, Lucas; Inácio, Luciano Marques; dos Santos, José Gonçalo (INFOCOMP Journal of Computer Science, 2016)
This paper presents the structure of a new system model for traffic inspection in Brazil. It shows the evolution of technological developments in order to help vehicles monitoring, and one of the approachs is the highway traffic monitoring. It was identified that this approach brings inconvenience for the society, like slow local traffic, complicating for the Traffic Agency, to accurately identify the cases that requires a traffic agent intervention. In this context, the project aims this market by optimizing agents' work, providing more effective local operations, improving accuracy on direct supervising to vehicles and providing a better life quality to citizens. In short words, it presents a solution to support traffic departments, regarding a direct approach, identification which vehicle should be inspected, type of inspection to be done, information of violations, resulting in improvement in the impact of vehicle traffic flow where the operation is done. Consequently, strategic decision-making can be done based with more accuracy. To build this solution, it is being applied the Rational Unified Process to the development of the software that integrates image capture with an IP Camera with embedded OCR.